Nickel‐Catalyzed 1, 1‐Difluoroethylation of (Hetero)aryl Halides with 1, 1‐Difluoroethyl Chloride (CH3CF2Cl). Issue 3 (3rd February 2020) - Liu, Jianchang; Zhang, Jida; Li, Xiangye; Wu, Chaolin; Liu, Hefu; Liu, Hui; Sun, Fenggang; Li, Yueyun; Liu, Yuying; Li, Xinjin
Abstract: 1, 1‐Difluoroethylated aromatic compounds are of increasing importance in agrochemicals and pharmaceuticals. The direct introduction of difluoroethyl (CF2 CH3 ) group(s) onto aromatic rings using CH3 CF2 Cl, an inexpensive and available raw material, still remains a great challenge because of the relatively inert C−Cl bond of CH3 CF2 Cl. Herein, we disclose a nickel‐catalyzed 1, 1‐difluoroethylation of (hetero)aryl halides with CH3 CF2 Cl. The reaction exhibits good functional‐group tolerance and is regarded as a practical method for synthesis of (1, 1‐difluoroethyl)arenes. Abstract : 1, 1 ‐Difluoroethylation : A nickel‐catalyzed 1, 1‐difluoroethylation of (hetero)aryl halides with 1, 1‐difluoroethyl chloride (CH3 CF2 Cl) has been successfully developed. This method exhibits good tolerance to functional groups, providing a general access to (1, 1‐difluoroethyl)arenes.